ASPEK HUKUM PERDATA DALAM PENYIARAN DAN PENAYANGAN IKLAN DI TELEVISI DI TVRI SUMUT - Hidayani, Sri (Jurnal Ilmiah Penegakan Hukum, 2016)
Television is one of the broadcasters in the form of broadcasts as set out in Article 1 paragraph 1 of Law 32 of 2002 on Broadcasting which reads "Broadcast is a message orseries of messages in the form of voice, images or sounds and images or graphic form,character , either interactively or not that can be received via the broadcast receivingdevice ". The existence of the television broadcast is a broadcast medium that uses sound toinfluence public opinion. As a result of the implementation of the television broadcastingwhich is the Public Broadcasting also obtain funds based ads created by advertisers on thetelevision. Basically an agreement will be implemented when the parties have agreed onthe main points of the agreement they are doing and they agreed that the signing will beforwarded in an agreement that has been agreed upon by each party. Agreement between the advertiser and the LPP TVRI SUMUT be made in writtenform. In which each party has the right and obligation. In this case the advertiser isobligated to pay for the ads that have been broadcast by the LPP TVRI SUMUT and theLPP TVRI SUMUT required to provide a report on the advertisers as evidence hascompleted its obligations. In an agreement in the event of a dispute sometimes promised. In terms ofadvertisement broadcasting agreement with the LPP TVRI SUMUT in case of disputessettled amicably if not completed resolved through the courts but, until now unheard of indefault.